ANALYSIS OF CIGARETTE DEMAND AMONG POOR HOUSEHOLDS IN INDONESIA: AN ISLAMIC ECONOMIC APPROACH - Monica, Yusnia; Ahsan, Abdillah; Djutaharta, Triasih; Amalia, Nadira (UI Scholars Hub, 2022)
Increasing Indonesia’s health and economic burdens generated by smoking habit require immediate stakeholder responses to reduce cigarette consumption. This study aims to examine and compare the changes in smoking behavior (i.e., the smoking status and the number of cigarettes consumed monthly) among zakat recipients (mustahik) and zakat payers (muzaki) caused by cigarette prices and income changes. Using a dataset from SUSENAS 2018 and conducted under kifayah approach (a poverty line approach in Islamic economics that will allow the observers to differentiate between muzaki and mustahik), this study employed two-part regression models. Results showed that an increasing income escalated cigarette consumption (ß = 0.761; 95% CI = 0.761, 0.762), but increasing cigarette prices reduced cigarette consumption (ß = -0.682; 95% CI = -0.683, -0.682). Mustahik household is more responsive toward changes as compared to muzaki ones. Mustahik household sensitivity towards cigarettes has important implications for zakat institutions in ensuring and monitoring zakat funds utilization among mustahik.